Self-regulated learning in physics: A comprehensive study of high school students through the lens of the Rasch Model - Fian Rifqi Irsalina; Lina Aviyanti; Yayan Rahayani (Momentum: Physics Education Journal, 2025)
This study investigates the Self-Regulated Learning (SRL) profile of high school students in physics within the Indonesian Merdeka Curriculum, which emphasizes student-centered and independent learning. A descriptive quantitative approach with the Rasch model using Winsteps software was employed to analyze data from 72 Grade 11 students at a state high school in Bandung, Indonesia. The Motivated Strategies for Learning Questionnaire (MSLQ) assessed SRL across various subdomains. The instrument demonstrated high reliability (Cronbach Alpha of 0.90), indicating strong internal consistency in measuring SRL abilities. The analysis revealed that most students had a moderate SRL profile, with strengths in Control of Learning Beliefs and Task Values, reflecting strong beliefs in the positive outcomes of their physics learning. However, areas such as Test Anxiety, Critical Thinking, and Effort Regulation showed lower scores, indicating areas for improvement. Additionally, Metacognitive Self-Regulation and Peer Learning enhanced students' understanding of physics. Based on these findings, it is recommended that educators design project-based learning experiences to leverage students' motivation and foster intrinsic interest in learning. Reducing test anxiety through hands-on learning and strengthening metacognitive skills through independent strategies can further support student growth. Encouraging peer learning and promoting critical thinking, mainly through Help-Seeking, are also crucial for enhancing SRL. This research provides valuable insights into SRL profiles in physics learning and offers practical strategies to improve student engagement and performance within the Merdeka Curriculum framework.